Pojęcie marki w literaturze i praktyce marketingowej - Wrona, Sylwia (Term 'Brand' in Literature and the Marketing Practice, 2006)
After over half the century of the collapse (times of the centrally planned economy), the 'brand' term has returned to Polish economy and social life, becoming an inherent factor perceived as one of the most important in purchase decision making. However, a question still remains whether all market participants interpret the term 'brand' in the same way. Does the term 'brand' mean the same for every consumer and every entrepreneur? The aim of the article is a review of the 'brand' term interpretations which occur in subject literature and economic practice. The results of the marketing research conducted by TNS OBOP AGENCY on 7-9 June 2003 are presented in the practical part of the article. It also includes the information from the questionnaire "The best brands in Poland" the research that has been conducted by the Institute of Polish Brand since 1996.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 84-94